علمی اسفار: اسلامی تعلیمات، مسلم روایت اور عصرِ حاضر میں ان کی ضرور ت و اہمیتStudy Tours: Islamic teachings, Muslim tradition and their need and Importance in Modern times (Al-Qamar, 2020)
It is not an exaggeration but fact that some decades ago skills and dexterities were attained through the usual study tours and it is pertinent to mention that the study tourists do not return until they get proficiency on their courses of study along with learning it by heart. Unfortunately, this element has become rare in today's world. This article highlights the importance of study tours in the light of Quran, Ḥadīth, practices of the companions, Sufis and other pious Muslims of the past and pronounces the importance of study tours in the present age. It concludes that it is the need of the hour to promote study tours and make attempts to achieve knowledge to the best possible extent in this way.
Keywords: Study tours; Islam; Muslim tradition; present age